Effect of colibacillosis or coccidiosis on expression of breast cancer resistance protein in small intestine and liver of chickens. Issue 1 (26th March 2013) - Su, L.; Dong, L.; Bughio, S.; Guo, M.; Wang, L.
<x xml:space="preserve">Abstract</x> Breast cancer resistance protein (BCRP, ABCG2) is a member of ABC (ATP‐binding cassette) transporter superfamily that occurs in a variety of tissues including liver and small intestine of animals. As BCRP is involved in drug absorption, distribution, and elimination, modulation of its expression may affect the clinical efficacy of drugs. However, little is known about the effects of coccidiosis or colibacillosis infection on the levels of BCRP expression in chickens. Here, we studied the effect of infection with Escherichia coli (E. coli) or Eimeriida mixture (E. necatrix and E. tenella) on the expression levels of ABCG2 mRNA and BCRP in the different segments of small intestine and liver in chickens. Expression of ABCG2 mRNA or BCRP was detected in the entire small intestine and liver of healthy chickens, and the expression levels in liver and ileum were significantly higher than duodenum and jejunum. Infection with E. coli or Eimeriida mixture resulted in significant decrease in ABCG2 mRNA and BCRP expression in liver, ileum, and jejunum, but not in duodenum, in comparison with noninfection control. The results indicate that coccidiosis or colibacillosis infection inhibits BCRP expression in chickens, which may consequently influence drug distribution and therapeutic efficacy.